Generalized model of electromigration with 1:1 (analyte:selector) complexation stoichiometry: part I. Theory - Dubský, Pavel; Müllerová, Ludmila; Dvořák, Martin; Gaš, Bohuslav (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
The model of electromigration of a multivalent weak acidic/basic/amphoteric analyte that undergoes complexation with a mixture of selectors is introduced. The model provides an extension of the series of models starting with the single-selector model without dissociation by Wren and Rowe in 1992, continuing with the monovalent weak analyte/single-selector model by Rawjee, Williams and Vigh in 1993 and that by Lelièvre in 1994, and ending with the multi-selector overall model without dissociation developed by our group in 2008. The new multivalent analyte multi-selector model shows that the effective mobility of the analyte obeys the original Wren and Row's formula. The overall complexation constant, mobility of the free analyte and mobility of complex can be measured and used in a standard way. The mathematical expressions for the overall parameters are provided. We further demonstrate mathematically that the pH dependent parameters for weak analytes can be simply used as an input into the multi-selector overall model and, in reverse, the multi-selector overall parameters can serve as an input into the pH-dependent models for the weak analytes. These findings can greatly simplify the rationale method development in analytical electrophoresis, specifically enantioseparations.
Keywords: koncentrace vodíkových iontů; Hydrogen-Ion Concentration; Models, Theoretical; stereoizomerie; Electrophoresis, Capillary; teoretické modely; Stereoisomerism; elektroforéza kapilární